Incident Atrial Fibrillation and Disability-Free Survival in the Cardiovascular Health Study - Wallace, Erin R. (J Am Geriatr Soc, 2016)
OBJECTIVES: To assess the associations of incident atrial fibrillation (AF) in relation to disability-free survival and the risk of disability. DESIGN: Prospective cohort study SETTING: The Cardiovascular Health Study PARTICIPANTS: 4046 participants aged 65 years and older and enrolled in fee-for-service Medicare followed between 1991 and 2009. Individuals with prevalent AF, Activities of Daily Living (ADL) disability, or a history of stroke or heart failure at baseline were excluded. MEASUREMENTS: Incident AF was identified by annual study ECG or using hospital discharge diagnosis or Medicare claims. Disability-free survival was defined as survival free of ADL disability (any difficulty or inability in bathing, dressing, eating, using the toilet, walking around the home, or getting out of a bed or chair). ADLs were assessed at annual study visits or by telephone interview. The association between incident AF and disability-free survival or the risk of disability was estimated using Cox proportional hazards models. RESULTS: Over an average of 7.0 years of follow-up, 660 individuals (16.3%) developed incident AF and 3112 (77%) became disabled or died. Incident AF was associated with decreased disability-free survival (HR for death or ADL disability=1.71, 95% CI 1.55, 1.90) and a higher risk of ADL disability (HR=1.36, 95% CI 1.18, 1.58) compared to individuals with no history of AF. This association persisted after adjustment for interim stroke and heart failure. CONCLUSION: These results suggest that AF is a risk factor for decreased functional longevity and disability in older adults, independent of other risk factors and comorbid conditions.